The Sustainable Development Goals in Social Work, ¿crossroads of a perpetual return in Colombia? - Contreras-Santos, Maira Judith (Prospectiva. Revista de Trabajo Social e Intervención Social, 2023)
Since the third decade of the 20th century, the intervention of Social Work has been complex depending on the goals of development, derived from international acts signed by the Colombian governments. Currently, putting the intervention of Social Work with the Sustainable Development Goals (SDG) into perspective is not simple either. To contribute to its understanding, this article compiles the results of the research that characterizes the contributions of Social Work in the cycles of public policies aimed at achieving the SDGs, proposed by its author at the XVI Colombian Congress of Social Work that was held at October 18 to 21, 2022 in Riohacha - Guajira.